Análise e prevalência de lesões cervicais não cariosas e suas relações com interferências oclusais : estudo in vivo - Castro, Christina Oliveira de (2012)
The aim of this study was identify the presence of non-carious cervical lesions (NCCL), in a random sample of individuals and correlating with the presence of occlusal interferences, as well as the risk factors involved in its development. There were evaluated 180 patients from Federal University of Espirito Santo, of both genders, aged 18 to 70 years. Involving 5192 teeth, which were examined by four investigators and one of them a Gold Standard Examiner. Used two study designs: observational cross-sectional and case-control study. Sought to identify NCCL and occlusal interferences. A data collection instrument was established in order to correlate socio-demographic and oclusal factors. Examinations concerning the presence of NCCL were made with a periodontal probe. The occlusal aspects of individuals, such as centric relation (CR), the maximum intercuspation (MHI) and excursive movements were surveyed. Regarding the number of individuals with NCCL, it was found that 129 of them had teeth with NCCL. In the total number of teeth, had 702 with NCCL. The distribution of lesions for each group of teeth, the premolars showed higher frequency, followed by the molars. There were 546 with occlusal interferences, and the most affected teeth were the first premolars. There was no positive correlation between the presence of occlusal interferences and NCCL.